2021
DOI: 10.3390/rs13214436
|View full text |Cite
|
Sign up to set email alerts
|

Marine Heatwaves in Siberian Arctic Seas and Adjacent Region

Abstract: We used a satellite-derived global daily sea surface temperature (SST) dataset with resolution 0.25 × 0.25∘ to analyze interannual changes in the Arctic Shelf seas from 2000 to 2020 and to reveal extreme events in SST distribution. Results show that the second decade of the 21st century for the Siberian Arctic seas turned significantly warmer than the first decade, and the increase in SST in the Arctic seas could be considered in terms of marine heatwaves. Analyzing the spatial distribution of heatwaves and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…We have found that sea ice and atmospheric dynamics primarily determine the variability of the Siberian shelf water state. We refer to [11] to show that early ice release and increased air temperature contributed to the formation of an anomalously high surface water temperature for this region, making it possible to consider these events as marine heatwaves [71]. For the present study, the most important is that the model shows the significant reduction in the sea ice cover in summer and sea surface temperature rise at the Siberian shelves during the last years of the second decade of the 2000s.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…We have found that sea ice and atmospheric dynamics primarily determine the variability of the Siberian shelf water state. We refer to [11] to show that early ice release and increased air temperature contributed to the formation of an anomalously high surface water temperature for this region, making it possible to consider these events as marine heatwaves [71]. For the present study, the most important is that the model shows the significant reduction in the sea ice cover in summer and sea surface temperature rise at the Siberian shelves during the last years of the second decade of the 2000s.…”
Section: Discussionmentioning
confidence: 96%
“…As a member of the international project FAMOS (Forum for Arctic Modeling & Observational Synthesis, [67]), the model was tested in coordinated modeling studies and compared with observational data [68][69][70]. Recent studies on the SibCIOM simulation [11,45] are closely connected with the present investigation. We have found that sea ice and atmospheric dynamics primarily determine the variability of the Siberian shelf water state.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Permafrost is widespread in the Arctic region, both in the continental region and in the vast areas of the shallow shelf of the Arctic seas [1][2][3]. A large amount of methane can be found in permafrost in a hydrated form [4].…”
Section: Introductionmentioning
confidence: 99%